Assessment of caecal parameters in layer hens fed on diets containing wheat distillers dried grains with solubles - White, Gavin A.; Richards, P.J.; Wu, S.; Mellits, K.H.; Wiseman, J. (Taylor & Francis, 2015)
There is much interest in quantifying the nutritional value of UK wheat distillers dried grains with solubles (W-DDGS) for livestock species. A study was designed to evaluate caecal parameters (pH, short chain fatty acids (SCFAs) and bacterial diversity) in layer hens fed on balanced diets containing graded concentrations of W-DDGS. A total of 32 layer hens (Bovans Brown strain at 27 weeks of age) were randomly allocated to one of 4 dietary treatments containing W-DDGS at 0, 60, 120 or 180 g/kg. Each treatment was fed to 8 replicate individually housed layer hens over a 5-d acclimatisation period, followed by a 4-week trial. Individual feed intakes were monitored and all eggs were collected daily for weeks 2, 3 and 4 of the trial, weighed and an assessment of eggshell “dirtiness” made. All hens were culled on d 29 and caecal pH and SCFAs measured. Polymerase chain reaction denaturing gradient gel electrophoresis of the bacterial 16 S rDNA gene was used to assess total bacterial diversity of luminal caecal content from hens fed the 0 and 180 g W-DDGS/kg diets. Unweighted pair group method with arithmetic mean (UPGMA) dendrograms were generated from DGGE banding patterns. Increasing W-DDGS dietary concentrations resulted in a more acidic caecal environment. Caecal SCFAs were unaffected by diet aside from a quadratic effect for molar proportions of isobutyric acid. Diversity profiles of the bacterial 16S rRNA gene from luminal caecal contents were unaffected by W-DDGS inclusion. The results of the current study suggest that W-DDGS can be successfully formulated into nutritionally balanced layer diets (supplemented with xylanase and phytase) at up to 180 g/kg with no detrimental effects to the caecal environment.